GAYA BAHASA PERBANDINGAN PADA LIRIK LAGU DALAM ALBUM RIUH KARYA FEBY PUTRI - Putri, Salsa Bila Eka; Hidayatullah, Syarif (LPPM Universitas PGRI Silampari Lubuklinggau, 2023)
The phenomenon of indie music in society is currently being favored by music listeners in Indonesia. Indie music is in demand by listeners, because it uses poetic language in each of its lyrics. The lyrics contain the use of figurative language. One of them was performed by Feby Putri who is a well-known indie singer in Indonesia. The research was conducted with the aim of finding the style of language contained in the song lyrics of the Riuh album created by musician Feby Putri. Content analysis was used in this study as a research method. The results of this study found that the Riuh album by Feby Putri had 10 song titles containing 4 types of comparative figurative language in the form of metaphors, parables or similes, personification and pleonalism or tautology